A low VSWR UWB microstrip antenna based on circular patch topology with partial ground plane / Mohd Aizat Sulaiman - Sulaiman, Mohd Aizat (2011)
Ultra Wideband (UWB) Microstrip Antenna consisting of a circular monopole patch with l0dB return loss bandwidth from 4.42 to 7.72 GHz and with a maximum VSWR = 1.19 is proposed. This antenna has been designed on FR4 printed circuit board (PCB) with overall size of 32 x 32 x 0.8 mm3 and dielectric substrate er = 4.7. This antenna operated at 5GHz centre frequency and was designed by using CST Software based on the 50J2 characteristic impedance for the transmission line model.